Hybrid System with Biomethanation for Wind Energy Accumulation in the Baltic Countries. (August 2015) - Blumberga, D.; Vigants, E.; Romagnoli, F.; Blumberga, A.; Kalnins, S.N.; Veidenbergs, I.
Abstract: Renewable electrical energy use has great advantages, especially in case of solar and wind energy. Among these – resource sustainability is the biggest advantage. Some renewable energy resources are related to the irregularity of the energy source. One of the most promising technologies is biogas biomethanation with hydrogen, the model of which is analyzed in this article. The methodology developed allows one to analyze the broad spectrum of hybrid systems with biomethanation for wind energy accumulation where the accumulation of wind energy potential, on the one side, meets the interests of the biogas station which can utilize this energy.